9. An Analysis of the Vocal Ensembles from the Opera "I Puritani" by Vincenzo Bellini - Simionescu Cristina (Sciendo, 2018)
I Puritani is the masterpiece that crowned the creation of the Italian composer Vincenzo Bellini, being remarked and appreciated for the richness of his melodicity and profound symbols filled with the inspiration and creativity of a creator. This was the last of the ten works composed by Bellini, whose disappearance was premature, at only 33 years, but the passion and talent with which he created revealed a work dominated by essence and emotion, which establishes a close connection between chant and the poetic text, providing new expressive valences to the lyrical universe. The extremely difficult and demanding vocal writing raises serious challanges, the Bel-canto style meaning not only a "beautiful chant" but also a difficult texture, a certain specific phrasing and a spread of spectacular acute tones.